The influence of cultural practices on the HIV and AIDS pandemic in Zambia - Moyo, Nolipher (HTS teologiese studies, 2011)
Culture plays a significant role in people’s lives in Zambia and in Africa as a whole. Consequently, there is a need to take Zambian or African culture seriously in order to look at the salient elements of cultural practices in rites of passage that influence the spread of HIV and AIDS. This article analyses four rites of passage associated with birth, puberty, marriage and death. There are numerous rites of passage in Zambian culture. Some of these rites help to curb the spread of HIV and AIDS, whilst others exacerbate the spread of the virus. Using the Reformed Church in Zambia Bible Study Method of Subgroups, discussions were held that allowed victims of cultural practices to tell their stories using the narrative model. This article sought to shed light on cultural practices that exacerbate HIV and AIDS and more importantly, provide culturally sensitive alternatives to these harmful practices.